TAKE-HOME RATIONS ON PRE-PRIMARY PUPILS’ ENROLLMENT IN PUBLIC PRIMARY SCHOOLS IN SABATIA SUB-COUNTY, VIHIGA COUNTY, KENYA - Kinagu, Judith; Ayaga , Geoffrey; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
Food provision has been seen as critical to the successful learning of pre-primary pupils. Even though the programs were, aimed at increasing student enrolment and retention, they were, executed with varying degrees of success across the country. Thus, the purpose of the study was to evaluate influence of take-home rations on pre-primary pupils’ enrollment in public primary schools in Sabatia Sub-County, Vihiga County, Kenya. It adopted a descriptive survey research design, with a target population of 571 persons including 33 Head teachers, 524 Teachers and 14 Members of the county assembly Board. The sample size of 234 persons was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and interview guides. The instruments were validated by the supervisors. Quantitative data was analyzed using descriptive and inferential statistics and presented in tables, while qualitative data analyzed in themes and sub themes and presented using quotations. The study established that school feeding programme like take-home rations, on-site meals, home-grown and community school influence pre-primary pupils’ enrollment in public primary schools. It was therefore recommended that there should be a consideration of different modalities of school feeding programme like take-home rations, on-site meals, home-grown and community based as this will enhance pre-primary pupils’ enrollment in public primary schools. The information provided by this research will benefit policymakers, community members and academicians.